2019
DOI: 10.1111/ele.13435
|View full text |Cite
|
Sign up to set email alerts
|

Mismatched outcomes for biodiversity and ecosystem services: testing the responses of crop pollinators and wild bee biodiversity to habitat enhancement

Abstract: Supporting ecosystem services and conserving biodiversity may be compatible goals, but there is concern that service‐focused interventions mostly benefit a few common species. We use a spatially replicated, multiyear experiment in four agricultural settings to test if enhancing habitat adjacent to crops increases wild bee diversity and abundance on and off crops. We found that enhanced field edges harbored more taxonomically and functionally abundant, diverse, and compositionally different bee communities comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 91 publications
0
34
0
Order By: Relevance
“…If native flora are planted interspersed among the apple trees, this may encourage native bees to move into the orchards and also forage on the apple flowers (Campbell et al 2017;Wu et al 2019). Even if this does not result in spillover into apples (Nicholson et al 2020), supporting bee biodiversity is important for wildflowers in native ecosystems and the ecosystem services these habitats provide (Kremen et al 2007) and also has high intrinsic value (Kleijn et al 2015;Prendergast 2020a). The floral associations of native bees observed in the present study are similar to those by , who found that Halictidae visited a taxonomically diverse range of flowers, and native Fabaceae and Ericaceae were important floral resources for a range of native bee species in Tasmania.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If native flora are planted interspersed among the apple trees, this may encourage native bees to move into the orchards and also forage on the apple flowers (Campbell et al 2017;Wu et al 2019). Even if this does not result in spillover into apples (Nicholson et al 2020), supporting bee biodiversity is important for wildflowers in native ecosystems and the ecosystem services these habitats provide (Kremen et al 2007) and also has high intrinsic value (Kleijn et al 2015;Prendergast 2020a). The floral associations of native bees observed in the present study are similar to those by , who found that Halictidae visited a taxonomically diverse range of flowers, and native Fabaceae and Ericaceae were important floral resources for a range of native bee species in Tasmania.…”
Section: Discussionmentioning
confidence: 99%
“…Even if this does not result in spillover into apples (Nicholson et al . 2020), supporting bee biodiversity is important for wildflowers in native ecosystems and the ecosystem services these habitats provide (Kremen et al . 2007) and also has high intrinsic value (Kleijn et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our study helps fill this gap, but caveats are warranted. First, bee diversity and crop pollination may not be compatible management goals (Nicholson et al 2020). Diversification as employed here had a positive population level effect for B. impatiens (a regionally dominant crop pollinator), but did not change the overall diversity of pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…As ecological restoration aims to restore all components of ecosystems, ecosystem functions and services, the effect of provenance choice on interacting biota including herbivores and pollinators should not be neglected. This is especially the case in projects that aim on supporting pollinators in agricultural landscapes (Nicholson et al 2020; Krimmer et al 2019; M’Gonigle et al 2015). In this context, attention is usually paid to the selection of particular plant species that are beneficial to pollinators, but within-species variability of these plants is largely neglected (M’Gonigle et al 2017; Williams & Lonsdorf 2018; Nichols et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to herbivores, the effect of plant provenance on pollinators is less known. Pollination is an important ecosystem service and many restoration efforts aim to promote pollinators in the landscape (Nicholson et al 2020; Krimmer et al 2019; M’Gonigle et al 2015). In this context, attention is paid to the selection of plant species that promote pollinators, but the variability within these plant species is largely ignored (M’Gonigle et al 2017; Williams & Lonsdorf 2018; Nichols et al 2019).…”
Section: Introductionmentioning
confidence: 99%